Characteristics of Qur’ānic Textuality; “al-Nasḵ” - Abbasi, Muhammad Zubair (Journal of Islamic and Religious Studies, 2017)
Since the “text” has received attention of all modern and post modern scholars and linguists, it has been changed. This “text” has different segments, some of them are applicable to Holy Qur’ān on the one hand, on the other hand there are some un-applicable too in connection of two textual boundaries of the “text”; bounded and un-bounded. From here many scholars declare that modern defined textual theory is totally un-applicable to Holy Qur’ān. Therefore, many Qur’ānic commentators and scholars refused “Intertextuality” with its all aspects. Anyhow some other scholars allow “Intertextuality” to be applied to Holy Qur’ān because of many Qur’ānic scholars have been interpreting this sacred text using the structural methods upon which contextual and intertextual phenomena and all the relevant conceptual components of this are based, this research intends elaboration of such dimensions of Qur’ānic “Intertextulaity” and “Textuality”, in particular, the Qur’ānic textulaity; “al-Nasḵ”; abolition, deletion and abrogation.